Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fphys.2017.00304
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Cough during Exercise Is Less Frequent in Healthy Children than Adults. Role of the Development and/or Atopy?

Abstract: Cough is typically associated with physical activity in children with asthma, but the characteristics of the relationship between cough and exercise has not been established under physiological conditions. The aim of the study was to describe the effect of exercise on the reflex cough response elicited by a single breath of capsaicin in non-asthmatic children. A group of non-asthmatic adults was studied as reference. Thirty children and 29 adults were recruited. The cough reflex sensitivity to capsaicin was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Capsaicin nebulization was used as an intervention method in our study and was shown to be more effective in removing sputum and preventing infection compared to conventional airway management procedures. Capsaicin nebulization-induced cough has been used in healthy adults, children, and the elderly (Brandimore et al, 2017;Demoulin-Alexikova et al, 2017), as well as in patients with pathological cough, hypertension, and cervical marrow injury. It has also been used to induce reflexive coughing in stroke patients (Hegland et al, 2016;Kulnik et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capsaicin nebulization was used as an intervention method in our study and was shown to be more effective in removing sputum and preventing infection compared to conventional airway management procedures. Capsaicin nebulization-induced cough has been used in healthy adults, children, and the elderly (Brandimore et al, 2017;Demoulin-Alexikova et al, 2017), as well as in patients with pathological cough, hypertension, and cervical marrow injury. It has also been used to induce reflexive coughing in stroke patients (Hegland et al, 2016;Kulnik et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Capsaicin is a component extracted from cayenne pepper (Sharma et al, 2013), which is commonly used as a non-acid-tussive agent to experimentally induce cough (Morice et al, 2007). Capsaicin nebulization to induce cough has been used in healthy adults (Brandimore et al, 2017;Demoulin-Alexikova et al, 2017) and patients (Duricek et al, 2018;Ferenc et al, 2018). Similarly, citric acid, a representative of acid tussives, could also be used to stimulate cough .…”
mentioning
confidence: 99%
“…One study examined the capsaicin cough sensitivity and found that exercise reduced cough sensitivity in all healthy adults but only in approximately 80% of healthy children. 10 Although the reason for this difference is not known, a higher incidence of personal and familial atopy may be present in children who did not show a reduction in cough during exercise compared with children who did. 10 Another aspect in cough-specific physiological maturation influence is the age-and sex-related differences in cough sensitivity.…”
Section: Childrenmentioning
confidence: 99%
“…10 Although the reason for this difference is not known, a higher incidence of personal and familial atopy may be present in children who did not show a reduction in cough during exercise compared with children who did. 10 Another aspect in cough-specific physiological maturation influence is the age-and sex-related differences in cough sensitivity. In prepubertal children, cough sensitivity is similar in boys and girls and therefore not influenced by sex.…”
Section: Childrenmentioning
confidence: 99%
“…The pathophysiology of cough during exercise remains unclear but undoubtedly involves numerous mechanisms suggesting that cough exhibits plasticity at both peripheral and central levels (Bonham et al, 2004;Widdicombe and Singh, 2006;Aggarwal et al, 2018). Previous studies have proven that CR is decreased during exercise in healthy subjects (Lavorini et al, 2010;Demoulin-Alexikova et al, 2017) as well as in animal models (Poussel et al, 2014), even the precise underlying mechanisms are still debated. In contrast, CR sensitivity during exercise was unchanged (i.e., lack of downregulation) in ovalbumin (OVA)-sensitized rabbits (eosinophilic bronchial inflammation mimicking classical asthmatic inflammation) (Tiotiu et al, 2017), suggesting the contribution of bronchial eosinophilic inflammation in the modulation of CR in asthmatics during exercise.…”
Section: Introductionmentioning
confidence: 99%